Evidence for increasing incidence of abnormalities of the human testis: a review. - Giwercman, A (1993)
Recent reports have suggested that the incidence of genitourinary abnormalities in human males has increased during the past 50 years, including congenital abnormalities such as cryptorchidism and hypospadia, which seem to be occurring more commonly. Also, the incidence of testicular cancer has increased 3- to 4-fold since the 1940s. This increase seems to be worldwide including countries with a very high frequency of testicular neoplasia as well as those in which this cancer is rather uncommon. It has also been postulated that semen quality has been decreasing for the last half century. A recent study showed that the average sperm density has decreased significantly from 113 million/mL in 1940 to 66 million/mL in 1990. The mean seminal volume has also declined, indicating that the decrease in the total sperm count is even more pronounced than the fall in sperm density would indicate. The remarkable increase in frequency of testicular abnormalities over a relatively short period of time may be due to environmental rather than genetic factors. There is an epidemiological link between the occurrence of different testicular abnormalities. Therefore, common prenatally acting etiological factors with adverse effects on the fetal male gonad might be suspected. However, postnatal influences may also have a deleterious effect on male fertility. From the reproductive point of view, an increased impact on the human male gonad is of concern.